Opioid use during Pregnancy: An Analysis of Comment Data from the 2016 Pregnancy Risk Assessment Monitoring System Survey. Issue 1 (December 2022) - O'Connor, Megan; Czarnik, Michaila; Morrow, Brian; D'Angelo, Denise
ABTSTRACT: Background : Opioid misuse during pregnancy has been associated with adverse infant outcomes including preterm birth, stillbirth, and neonatal opioid withdrawal syndrome. The Pregnancy Risk Assessment Monitoring System (PRAMS) is an on-going state-based surveillance system of maternal behaviors, attitudes, and experiences prior to, during, and after pregnancy. Methods : We analyzed qualitative comments related to opioid use during pregnancy collected in 2016 from an open-ended prompt at the end of the PRAMS survey in 35 states ( N = 40, 408). Key word searches were conducted on the open-ended responses ( n = 9, 549) to identify opioid-related content with an automated function using Microsoft Excel. All responses from the initial screening ( n = 1, 035) were manually reviewed, and 69 responses were confirmed to relate to the respondent's personal experience with opioid use during pregnancy. Content analysis was conducted by 3 independent coders; key themes were compiled, discussed, and finalized by the coding team. Results : Five key themes related to opioid use during pregnancy were identified: (1) gratitude for treatment, recovery, and healthy infants; (2) pregnancy as motivation to seek treatment; (3) difficulty finding prenatal care providers with training in substance use disorders; (4) concern about the effects of treatment on the infant; and (5) experiences of discrimination and stigma in the hospital around the time of delivery. Conclusions : Women may be aware of the potential impact of opioid use during pregnancy on the health of their infants and motivated to seek treatment. Findings may help inform new and ongoing initiatives designed to improve care and reduce stigma for women needing or seeking treatment.